TRANSFORMATION OF TECHNOLOGY ON LEARNING NOTATION NUMBERS THROUGH PARNUMATION 3.0 MEDIA - Risky Aswi Ramadhani; Itot Bian Raharjo (Universitas Sebelas Maret, 2017)
Based on the last observation in the learning process for childhood musical skill in PG-PAUD Nusantara PGRI Kediri University, we can conclude that the ability of the students in theories and practice is low. One of the example is the result of song particles in the form of number notations is not proportional. Because of that problem, we can make material of evaluation to increase the ability of students in the musical skill continually. Because of that reason, we need the best inovation in the learning process for making song particles in the form of number notations through